Decentralised Finance – wie die Tokenisierung die Finanzindustrie verändert; Decentralised Finance (DeFi): How Tokenisation is changing the financial industry - Volker Brühl (Wirtschaftsdienst, 2021)
Die Distributed Ledger- bzw. Blockchain-Technologie führt zu einer zunehmenden Dezentralisierung von Finanzdienstleistungen, die weitgehend ohne die Einschaltung von Finanzintermediären angeboten werden können. Dazu trägt wesentlich die "Tokenisierung" von Vermögensgegenständen, Zahlungsmitteln und Rechten bei, die verschlüsselt als Kryptowerte in verteilten Transaktionsregistern digital abgebildet werden können. Dieser Beitrag erläutert die Grundlagen und Anwendungsfelder dezentraler Finanzdienstleistungen mit Kryptowerten, die mittelfristig die gesamte Architektur des Finanzsektors verändern könnten. – – Advances in distributed ledger technology are leading to a growing decentralisation of financial services ("decentralised finance") that can be offered largely without intermediation by financial institutions. An important driver for this development is the ongoing tokenisation of assets, payments and rights, which enables the digital encryption of 'crypto assets' on distributed ledgers. This article elaborates the foundations and fields of application of decentralised financial services with crypto assets that could challenge the established business models of financial institutions. This trend not only affects payment systems based on controversial crypto currencies such as Bitcoin, but also exchange platforms, capital markets solutions and corporate financing. A rapidly growing ecosystem of start-ups, tech companies and financial institutions is emerging, yet this ecosystem lacks a consistent regulatory framework. The European initiative MiCA (Markets in Crypto Assets) points in the right direction but needs to be adopted soon to ensure the future competitiveness of the European financial sector.
Keywords: G10; G20; 330; Finanzsektor; Finanzdienstleistung; Blockchain